MAPPING TRADITION AND MODERNIZATION: A STUDY ON THE EVOLUTION OF COSTUMES OF THE TRIPURI AND REANG WOMEN IN TRIPURA - Roy, Gitanjali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Tripura is a land-locked state in Northeast India that comprises of multiple communities. Majorly dominated by the Tribal and Bengali communities, this state has witnessed drastic changes in its culture and heritage. Since partition, a huge demographic and ethnographic change has ushered in major challenges for the tribal communities. One such major change was witnessed in the evolution of Tripuri and Reang costumes. The traditional dresses of the communities faced historic challenges that questioned their personal and collective identity. The impact of westernization and modernization on Tripuri dressing culture shall be analysed in this paper. This paper shall also try to study how patterns of cloth and style of dressing have evolved due to the impact of global culture over the local culture. The reasons for the evolution shall be mapped through qualitative data collected from different people (of different communities) belonging to different parts of the state.